THE IMPACT OF THE KOREAN WAVE ON ARCHITECTURE IN INDONESIA - Arrum Sari, Attiya; Pratama, Ridho Haikal (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2024)
This study explores the influences of the Korean Wave on Indonesian architecture. This research uses descriptive qualitative methods. The findings reveal the integration of Korean design principles into Indonesian architecture, highlighting concepts like open spaces, multifunctional areas, natural lighting, and the use of materials such as wood. Inspired by both traditional and modern Korean houses, these elements emphasize flexibility, efficiency, and a connection to nature. The influence of Hallyu or Korean culture is also evident in architectural education, with students incorporating Korean aesthetics, symbols, and design approaches into their works. These designs not only reflect cultural exchange but also demonstrate how Korean cultural elements, including K-pop and traditional motifs, shape modern Indonesian architectural practices. This fusion of design tradition fosters innovation and enhances the global understanding of architecture.